Professional Boundaries in The Relationship Between Nurses and Patients in Healthcare Settings: A Scoping Review - Ni Putu Suryani; Hana Rizmadewi Agustina; Theresia Eriyani; Dyah Setyorini (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
This study aimed to identify and map material findings related to the concept of professional boundaries in the nurse-patient relationship based on the perspective of nurses. This study used a scoping review method according to the Arksey and O'Malley (2005) framework with PubMed, CINAHL, and SAGE as databases, and equipped with manual searches using a snowball technique to identify additional materials. It used major terms such as Nurse AND Understand AND Professional Boundaries AND Nursing Practice and several alternative terms. Eligible articles were analyzed using inductive content analysis. The results of the content analysis of 16 relevant articles discuss five categories of the concept of professional boundaries. Nurses have various understandings related to the concept of professional boundaries, especially related to the types of boundaries. Professional boundaries are defined as boundaries for maintaining a therapeutic relationship. Nurse competence is an important factor in the implementation process. Abstrak: Penelitian ini bertujuan untuk mengidentifikasi dan memetakan temuan materi terkait konsep batasan profesional dalam hubungan perawat-pasien berdasarkan perspektif perawat. Penelitian ini menggunakan metode scoping review menurut framework Arksey dan O'Malley (2005) dengan PubMed, CINAHL, dan SAGE sebagai database, serta dilengkapi dengan pencarian manual menggunakan teknik snowball untuk mengidentifikasi bahan tambahan dengan menggunakan kata kunci utama seperti Nurse AND Understand AND Professional Boundaries AND Nursing Practice dan beberapa istilah alternatif. Artikel yang memenuhi syarat dianalisis menggunakan analisis konten induktif. Hasil analisis menghasilkan 16 artikel relevan yang membahas lima kategori konsep batasan profesional. Perawat memiliki berbagai pemahaman terkait konsep batasan profesional, terutama terkait dengan jenis- jenis batasan. Batasan profesional didefinisikan sebagai batasan untuk mempertahankan hubungan terapeutik. Kompetensi perawat merupakan faktor penting dalam proses implementasi.